COMBINATION OF CONGENITAL HEART DEFECTS AND HP IN THE INITIAL SAMPLE OF FETAL ARRHYTHMIAS - Qobiljonova Shaxnoza Rustam qizi; Ergasheva Maftuna Farhod qizi; Nazirova Muattarxon Maʼrufjon qizi; Azimova Dildora Baxrom qizi (Modern American Journals, 2025)
Fetal arrhythmias occur in 1-5% of all pregnancies. Approximately 10% of all arrhythmias are accompanied by the development of hydrops fetalis and intrauterine mortality. Diagnosis and treatment of fetal arrhythmias is an interdisciplinary problem that has not yet been fully resolved. Malignant arrhythmias ( supraventricular tachycardia, atrial flutter, complete transverse block) combined with hydrops fetalis cause intrauterine death in 3-30% of cases. Transient arrhythmias (single ventricular and atrial extrasystole, sinus tachycardia) occur in 15-32% of cases, according to 1998 data, and do not require special treatment. According to Strasburger JF, 2020 , supraventricular tachycardia and complete block are diagnosed in 1 in 5,000 fetuses. According to Ferrer PL, 2020 , complete AV block is detected in 1:20,000 live births.